Course registration and examination validation using fingerprint technology / Khairul Wanis Ahmad - Ahmad, Khairul Wanis (Faculty of Information Technology and Quantitative Sciences, 2004)
This thesis project is about designing an integrated database system where the proposed system will provide reliable, verifiable, and convenient authentication system. As we know, biometric technologies are commonly used nowadays. Besides providing strong security, it also convenient to use. The fingerprint technology is cheaper and easy to implement compared to other biometrics technologies. This Course Registration and Examination Validation using Fingerprint Technology is designed to enhance the current Course Registration and Examination Validation at FTMSK. This enhancement is made to make this system more efficient and reliable.. For the course registration system, the proposed system will overcome the problem that we have faced with the current system. From the testing that have been made, this proposed system have countered the problem that exist from the current system. The proposed system with the fingerprint feature can make examination validation is strongly secure because no student can except to be authenticate before they enter the examination room. Besides provide security, this new system provides efficiency to both parties; student and invigilator.